Algal Flora of Nagdaha Lake, Lalitpur, Nepal - Parajuli, Bishnu Prasad (Himalayan Biodiversity, 2017)
This paper is a report of algal flora of Nagdaha Lake, Dhapakhel, Lalitpur. Algal Samples were collected out in the months of May, August and December 1996, from four different sampling sites of the lake. From the investigation, 25 different algal taxa belonging to 16 families were observed. Among them, 17 species were observed in summer and winter season while in rainy season 19 species were observed.